Investigating the Indoor and Outdoor Respirable Suspended Particulates of Coarse (PM10), Fine (PM2.5) and Ultrafine (PM1) - Mansor A.A.; Ghazali M.I.H.; Abdullah S.; Dom N.C.; Ahmed A.N.; Ismail M. (Universiti Putra Malaysia Press, 2023)
Introduction: Respirable Suspended Particulate (RSP) is a particularly serious indoor air pollution since at least a portion of particles ingested by humans can be permanently deposited in the respiratory tract. Analysis of indoor air quality in school classrooms is essential because the air quality can have a significant impact on the health and performance of children. Methods: The site selections were based on the surrounding activities of commercial and industrial areas. Instruments used for measuring parameters are Dust TraxTM DRX Aerosol II 8532 and Kanomax IAQ Monitor. Results: The study shows that the commercial area has a higher concentration of RSP compared to the industrial area. The I/O ratio value is higher at commercial area compared to industrial area with the value of PM10 = 3.065, PM2.5 = 3.222, PM1 = 3.261, CO2 =1.242, RH = 1.212, temperature = 0.891, and air movement = 1.072 for commercial area, and PM10 = 1.482, PM2.5 = 1.456, PM1 = 1.449, CO2 =1.116, RH = 1.134, temperature = 1.040, and air movement = 1.008 for the industrial area. For a commercial area, the indoor RSP is strongly correlated to all meteorological parameters with the value exceeding 0.5 except for CO2 has moderately correlated with the value is between 0.4 to 0.49, and wind speed has weak correlate with the value is less than 0.39 . Conclusion: : In conclusion, the classroom located in commercial is more polluted compared to the industrial area and the RSP is significantly influenced by meteorological factors. 2022 UPM Press. All rights reserved.